Comparison of Efficacy and Hemodynamic Stability of 0.5 % Isobaric Levobupivacaine and 0.5% Hyperbaric Bupivacaine in Old Age Patients Posted For Lower Limb Surgery under Spinal Anaesthesia - Neepa Patel; Bhumika J Chaudhari; Pratik D Patel; Malti Pandya (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Spinal anaesthesia, first introduced by August Bier in 1898, has evolved significantly with the introduction of bupivacaine and levobupivacaine. Bupivacaine is the most commonly used local anesthetic, while levobupivacaine and bupivacaine are equivalent but levobupivacaine have fewer cardiac side effects. Isobaric levobupivacaine is less toxicity and is used in various Anesthetic procedures. Geriatric patients are more susceptible to haemodynamic fluctuations due to changes in vertebrae structure, decreased cerebrospinal fluid volume, and nerve degeneration. This study aims to compare the safety profiles of hyperbaric bupivacaine and isobaric levobupivacaine in elderly patients during spinal anaesthesia for lower limb surgery. Materials and methods- The study was conducted at a tertiary health care center over a period of one year and six months, with 110 patients above 60 years of age, either sex, ASA grade III & IV, posted for lower limb surgeries. The total sample size was figured as 110 based on a previous study by Herrera R et al.5 The study involved pre-anaesthetic evaluation, laboratory investigations, and informed consent from all study subjects.The patients were divided into two groups: Group B received a 0.5% 3 ml hyperbaric injection of bupivacaine intrathecally, and Group L received a 0.5% 3 ml isobaric injection of Levobupivacaine intrathecally. The patients were monitored using standard monitors such as pulse oximeter for saturation (SpO2), noninvasive blood pressure monitoring (NIBP), and electrocardiogram (ECG). Sensory and motor assessments were performed immediately after positioning supine and recorded as 0 minutes. The study also assessed the duration of motor blockade, Bradycardia, and hypotension. Postoperatively, hemodynamic parameters, duration of analgesia, and total duration of sensory and motor block were assessed every 2 hourly for 6 hours & 4 hourly till 24 hours. Result- The study compared the heart rate and blood pressure of two groups after spinal anesthesia. Both groups had similar baseline heart rates, but after spinal anesthesia, there was a significant difference in heart rate. Group B had greater pulse rate variability, indicating a statistically significant difference. Systolic blood pressure was comparable in both groups, but the decrease was greater in group B compared to group A. Mean arterial blood pressure was comparable in both groups, but Group B experienced a greater decrease. The onset time of sensory block at T10 level was comparable between groups, but the maximum sensory block level was different. The duration of sensory block was longer in Group B, while the total duration of analgesia was longer in Group B. Group B had greater pulse rate variability, but no significant difference in mean arterial pressure. Conclusion- The study concluded that 0.5% isobaric levobupivacaine is more effective than 0.5% hyperbaric bupivacaine in elderly patients undergoing lower limb surgery due to its superior hemodynamic stability.